The effect of LEED certification on office rental values in China. (June 2021) - Li, Weilin; Fang, Guanyu; Yang, Liu
Highlights: A hedonic price model is established to study impacts of different factors on rents. Shanghai, Beijing and national markets have been contrastively analyzed. Rental premiums of LEED-certified buildings in Chinese markets are obvious. Different characteristics of Chinese markets are found compared to foreign markets. Abstract: With the increasing awareness of environmental protection, the real estate sector has proposed green buildings to achieve the sustainability of the building environment. Although the advantages of these sustainable features of green buildings are apparent, the effect of green buildings on the real estate economic values in China is not evident. This study aims to investigate whether and to what extent LEED certification can impact the rental values of the office market in China. This study analyzes an overall sample of China comprising 50 LEED-certified and 50 non-LEED offices and two local samples of Shanghai and Beijing each, based on a hedonic price model. The results suggest that the rental premium for LEED-certified in the China sample is 19.5%, while that in Shanghai and Beijing samples are 25.5% and 20.8%, respectively. Furthermore, other variables, such as utilization time, floors, construction area, building class, and GDP, are also correlated with rental values. As an early study on the impact of green certifications on the Chinese real estate market, this research provides investors with empirical data to evaluate the investment value of introducing green certifications and serves as a reference for future explorations of green certifications in the Chinese real estate market.